Yesterday's Heroes: Compensation and Risk at Financial Firms - CHENG, ING‐HAW; HONG, HARRISON; SCHEINKMAN, JOSÉ A. (Journal of Finance, 2015)
ABSTRACT Many believe that compensation, misaligned from shareholders’ value due to managerial entrenchment, caused financial firms to take risks before the financial crisis of 2008. We argue that, even in a classical principal‐agent setting without entrenchment and with exogenous firm risk, riskier firms may offer higher total pay as compensation for the extra risk in equity stakes borne by risk‐averse managers. Using long lags of stock price risk to capture exogenous firm risk, we confirm our conjecture and show that riskier firms are also more productive and more likely to be held by institutional investors, who are most able to influence compensation.